(untitled) (Research, Society and Development, 2021)
White spot lesions are a common clinical complication that affects dental esthetics and turn patients uncomfortable. An advantageous alternative to treat those lesions is the resin infiltration technique, that preserves healthy dental structure due its minimally invasive intervention. The patient had enamel hypoplasia on teeth 12 and 13, that was treated with an in-office bleaching and microabrasion followed by resin infiltration (Icon™). At the end of the procedure, it was noticed a color change, turning the spot unnoticeable on patient’s teeth. The main advantage of resin infiltration is to guarantee teeth tissue preservation treatment while reestablishing esthetics, even when deep lesions are presented.